Investigating the relationship between entrepreneurial orientation and iconic branding in South Africa's food retailing industry : a consumer perspective - Van Vuuren, Jurie Jansen (University of Pretoria, 2023)
Thesis (PhD (Entrepreneurship))--University of Pretoria, 2023.